Natural theology of Zinovy Otensky in the context of the Old Russian philosophical booklore - Shpakovskiy, Mikhail (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. I, Bogoslovie, filosofii͡a, 2020)
This article deals with the fi rst Russian proofs of God’s existence which were proposed by Zinovy Otensky in the Demonstration of the Truth. The author of the article believes that F. V. Kalugin’s and R. Mainka’s studies are not comprehensive. They did not take into account the historical and philosophical context of these proofs and therefore could not give an evaluation that would be relevant to the historical context. This article evaluates each of Zinovy’s proofs following the reconstruction of his philosophical views. The description of the latter is made more precise, which allows one to identify their sources in the philosophical booklore of Ancient Rus’ and to reconstruct the relevant historical and philological background of these proofs. Zinovy himself proposed fi ve proofs of God’s existence. They were designed to disprove the theory of independent emergence of all being which was ascribed to the famous heretic Theodosius Kosoy. Zinovy’s proofs have a syllogistic structure and a detailed substantiation of the prerequisites. Proof 1: all kinds of living beings are created. This proof is founded on the principle of immutability of created species which goes back to the 2nd Oration against the Arians by Athanasius of Alexandria. Proof 2: all being was created. This argument draws on the conception of motion and rest going back to Aristotle. This doctrine is expounded in the Dialectics by John of Damascus and in scholia on the Corpus Areopagiticum. Proof 3: man knows and seeks God by nature. This elaborates one of the statements of Damascene’s Theology. Proof 4: all beings are subject to passions and change and therefore could not appear independently. This proof is illustrated by the texts that contain Aristotelian doctrine of motion and aff ect. Proof 5: the order of the four elements evidences the presence of the Arranging One. This proof is based on the classical theory of elements and their order and harmony. The article concludes that Zinovy’s philosophical views were infl uenced by the tradition of Aristoteles Slavicus. One can claim that proofs 1 and 2 are original, whereas 3, 4, 5 are original developments of Greek prototypes.